Tanggung Gugat Pemegang Hak Cipta Terhadap Perbuatan Melawan Hukum Pelanggaran Hak Cipta - Eko Rial Nugroho; Wahyu Priyanka NP (JIPRO: Journal of Intellectual Property, 2019)
PT. ISM and FIFA have made and signed License Agreement in May 5th, 2011. The License Agreement related to delegation of certain rights of broadcasting which related on XX edition from football tournaments and other FIFA events. Based on this exclusivity, there are no other parties (Include but not limited to the broadcaster), who have right to (but not limited to) do socialization, marketing, and supervision of permission to use the 2014 Brazil World Cup broadcast commercially in commercial places. However, a party namely PT. SSM alleged to do act against the right to broadcast or airing or hold a Nonton Bareng event of 2014 Brazil World Cup commercially without having permission from PT. ISM. As a result of broadcasting the 2014 Brazil World Cup by PT. SSM, PT. ISM felt material and immaterial losses. The purpose of this study is to figure out whether Copyright infringement can be categorized as an unlawful act and to know how the legal protection for the Copyright license holder of unlawful act in the form of Copyright infringement.This Study is a normative legal study with qualitative analysis. This study concluded that PT. SSM has committed an unlawful act in the form of a Copyright infringement and the legal protection has given to copyrights license holder by taking legal action in the form of a lawsuit to the Commercial Court and requesting for compensation of unlawful act committed by PT. SSM